2020
DOI: 10.1016/j.jas.2020.105123
|View full text |Cite
|
Sign up to set email alerts
|

Pyrotechnological connections? Re-investigating the link between pottery firing technology and the origins of metallurgy in the Vinča Culture, Serbia

Abstract: The present paper re-examines the purported relationship between Late Neolithic/Early Chalcolithic pottery firing technology and the world's earliest recorded copper metallurgy at two Serbian Vinča culture sites, Belovode and Pločnik (c. 5350 to 4600 BC). A total of eightyeight well-dated sherds including dark-burnished and graphite-painted pottery that originate across this period have been analysed using a multi-pronged scientific approach in order to reconstruct the raw materials and firing conditions that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 49 publications
0
29
0
Order By: Relevance
“…This metal construct is still frequently dominant in scholarship seeking to define the (elite) socio-economic dynamics of prehistoric communities, despite the fact that other materials such as ceramics, flint, polished stone, obsidian and spondylus (e.g. Amicone et al 2019;Amicone et al 2020a;Amicone et al 2020b;Ifantidis & Nikolaidou, 2011;Klimscha, 2016;Milić, 2015;Spataro, 2018;Whittle et al 2016;Windler 2018) were also comparably, or much more extensively, sourced, shaped, traded and/or deposited in settlements and graves both prior to and, later, along with metal objects. It is evident that, especially in the last decade, many major Balkan Neolithic/Chalcolithic projects have explicitly sought to push beyond traditional metal-orientated perspectives, especially given the significantly increased scale and depth of understanding of the non-metallurgical archaeological andenvironmental record in recent years.…”
Section: Scholarship In Early Balkan Metallurgymentioning
confidence: 99%
See 2 more Smart Citations
“…This metal construct is still frequently dominant in scholarship seeking to define the (elite) socio-economic dynamics of prehistoric communities, despite the fact that other materials such as ceramics, flint, polished stone, obsidian and spondylus (e.g. Amicone et al 2019;Amicone et al 2020a;Amicone et al 2020b;Ifantidis & Nikolaidou, 2011;Klimscha, 2016;Milić, 2015;Spataro, 2018;Whittle et al 2016;Windler 2018) were also comparably, or much more extensively, sourced, shaped, traded and/or deposited in settlements and graves both prior to and, later, along with metal objects. It is evident that, especially in the last decade, many major Balkan Neolithic/Chalcolithic projects have explicitly sought to push beyond traditional metal-orientated perspectives, especially given the significantly increased scale and depth of understanding of the non-metallurgical archaeological andenvironmental record in recent years.…”
Section: Scholarship In Early Balkan Metallurgymentioning
confidence: 99%
“…It is therefore not uncommon to see debates on the connections between the emergence of metallurgy and the Gradac phase of Vinča culture ceramic sequence, or the relationship between the development of metallurgy and the widespread graphite painted decoration on the ceramics of the Kodžadermen-Gumelniţa-Karanovo (KGK) IV cultural complex (e.g. Amicone et al 2019Amicone et al , 2020bGarašanin, 1995;Jovanović, 1971Jovanović, , 1994Jovanović, , 2006Radivojević & Kuzmanović-Cvetković, 2014;Radivojević et al 2010b;Renfrew, 1969;Spataro & Furholt, 2020;Spataro et al 2019;Todorova, 1995;Todorova & Vajsov, 1993). As is now widely acknowledged in Balkan and world prehistory, the creation of spatial and temporal frameworks through the identification of similarities and differences in materials and practices continues to evade researchers; straightforward explanations are unlikely (cf.…”
Section: Scholarship In Early Balkan Metallurgymentioning
confidence: 99%
See 1 more Smart Citation
“…7). This means that pottery kilns would have been widespread in what Sherratt (1976) termed 'metropolitan Vinča sites' in the main lowland valleys -a sign of at least part-time specialisation in pottery production (contra Amicone et al 2020). Nonetheless, in the recent review of the relationship between dark burnished ware production and copper smelting, Amilcone et al (2020,120) conclude that while "it is not possible to exclude that a certain degree of specialisation in pottery production existed among Vinča potters, no convincing arguments have been brought in thus far that demonstrated that this craft was a highly specialised activity carried out by professional figures that had privileged access to resources and technology".…”
Section: Intensification Of Productionmentioning
confidence: 99%
“…Turning to pottery, most Vinča fine wares were fired to a dark burnished surface, varying within sites between light grey and black in colour and degree of burnish / polish, and, to judge from available ceramic analyses (e.g., Spataro, 2017;Amicone et al, 2019Amicone et al, : 2020 Amicone, this issue), fired for the most part to 800 -900 0 C by non-specialist potters (but see above, p. xxx). The aesthetic result of the technical achievements of pottery firing was a startingly attractive object that shone like an obsidian core, putting all other ceramics into the shadow.…”
Section: Cultural Integrationmentioning
confidence: 99%